1993
DOI: 10.1099/00207713-43-1-174
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of Phosphatase Activity among Enterobacterial Species

Abstract: The phosphatase activities of cells of representative enterobacterial species were studied after cells were grown in a chemically defined medium with variations in the amounts of phosphates and in pH (4.00 to 9.00). All strains of a given species demonstrated similar acid phosphatase activities after growth in the presence or absence of phosphates. In contrast, alkaline phosphatase was produced only by some species, and it was also strongly influenced by the presence of either glycerophosphate or Pi in the med… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

1994
1994
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 9 publications
0
7
0
Order By: Relevance
“…On the other hand, ACP was produced in large quantities by Klebsiella and Morganella , as well as Providencia stuartii . For the Klebsiella species, production varied from 11.63 to 18.66 U L −1 min −1 , which was 17.79 to 11.09 times less than the maximal activity obtained by the strain under study, whereas for Morganella morganii and Providencia stuartii , production ranged from 170 to 675 and 1300 to 1686 U L −1 min −1 , respectively 28 .
Figure 7 ( a) Monitoring of B. haynesii strain ACP1 growth and acid phosphatase productivity in a 7 L stirred-tank bioreactor under uncontrolled pH conditions, and (b) online data (dissolved oxygen percentage, agitation, aeration, and pH) as a function of time during batch fermentation in the bioreactor under uncontrolled pH conditions.
…”
Section: Resultsmentioning
confidence: 69%
“…On the other hand, ACP was produced in large quantities by Klebsiella and Morganella , as well as Providencia stuartii . For the Klebsiella species, production varied from 11.63 to 18.66 U L −1 min −1 , which was 17.79 to 11.09 times less than the maximal activity obtained by the strain under study, whereas for Morganella morganii and Providencia stuartii , production ranged from 170 to 675 and 1300 to 1686 U L −1 min −1 , respectively 28 .
Figure 7 ( a) Monitoring of B. haynesii strain ACP1 growth and acid phosphatase productivity in a 7 L stirred-tank bioreactor under uncontrolled pH conditions, and (b) online data (dissolved oxygen percentage, agitation, aeration, and pH) as a function of time during batch fermentation in the bioreactor under uncontrolled pH conditions.
…”
Section: Resultsmentioning
confidence: 69%
“…ALP is a vital enzyme involved in the mineral formation of the natural bone [22]. The enzyme activity ideally triggered the release of inorganic phosphate ions in the media, which further reacted with calcium ions to form hydroxyapatite crystals [23]. When live The EDS spectrum of the nanocomposite detected traces of mineral ions such as strontium, magnesium, zinc and sodium on the SNHA membranes.…”
Section: Scanning Electron Microscope Studymentioning
confidence: 99%
“…Therefore, the simple measurement of phosphatase activity of whole cells or of crude cell extracts using chromogenic substrates is not expected to be highly informative. However, gross differences in the pattern of phosphatase production can also be detected using this simple approach [18,26,44], which is suitable for analysing a considerable number of strains. In fact, measurement of total phosphatase activity produced by different members of the family Enterobacteriaceae showed that Pro6idencia stuartii and Morganella morganii are able to produce a highlevel P i -irrepressible acid phosphatase (HPAP) activity (indicated as HPAP phenotype), unlike most other enterobacterial species, which produce only low to moderate levels of acid phosphatase activity under similar conditions [18,26].…”
Section: Analytical Tools For Studying Bacterial Nsapsmentioning
confidence: 99%